Three-Year Follow-Up Study Exploring Metacognition and Function in Individuals With First Episode Psychosis - Wright, Abigail C.; Davies, Geoff; Fowler, David; Greenwood, Kathryn (Frontiers in Psychiatry, 2019)
Introduction: Research has demonstrated that functional outcome in psychosis is predicted by factors such as neurocognition, functional capacity, symptoms and, more recently, metacognition. Metacognitive ability has been demonstrated to mediate between neurocognition and functional outcome in First Episode Psychosis (FEP). Whether metacognition also predicts longer-term recovery in first episode is unknown. This study assessed whether neurocognition, functional capacity and metacognitive ability in FEP predicted functional outcome three years later. Methods: Eighty individuals with First Episode Psychosis were re-contacted after an average three years (range: 26-45 month follow-up) from baseline. Twenty-six participants (33%) completed neurocognitive measures, metacognition, functional capacity, functional outcome (hours spent in structured activity per week) and psychopathology at baseline and at follow-up. Results: Individual regression analyses demonstrated neurocognition, functional capacity and metacognitive ability at baseline significantly predicted functional outcome at three years. However, when baseline functional outcome was controlled, only metacognitive ability was a significant predictor of change in functional outcome from baseline to follow-up, p<.001. This model explained 72% (adjusted r² = .69) of the variance in functional outcome at follow-up. Negative symptoms did not change the model. Discussion: This study demonstrated that better metacognitive ability significantly predicted improvement in functioning in FEP across a 3-year period. This highlights the potential value of clinical interventions that focus on improving metacognitive ability at first point of illness to maximize recovery.